Association of socioeconomic status with sex ratio at live birth in individuals living in the slums of Sholapur city, India - Ahankari, Anand S.; Fogarty, Andrew W. (Dipika Charan, 2015)
Background: The existence of female feticide in India is well known. However, limited data are available on the association of socioeconomic status (SES) on sex ratio at live birth in disadvantaged populations, despite the fact that 33% of the population of India live on less than $1.25 per day.